2022
DOI: 10.1038/s41598-022-08754-4
|View full text |Cite
|
Sign up to set email alerts
|

Mandible shape variation and feeding biomechanics in minks

Abstract: European and American minks are very similar in ecology, behavior and morphology. Both species hunt terrestrial vertebrates and aquatic prey, but the American mink is a more generalist predator which, among other factors, allows it to outcompete the European mink in areas where it has been introduced. We used 3D geometric morphometrics and estimates of muscle mechanical advantage to assess the degree of variation in mandibular morphology, and to determine whether such variation reflects dietary differences bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…A longer coronoid process and an rostrally expanded masseteric fossa correspond to increased muscle attachment areas and longer in‐levers, which is indicative of a higher mechanical lever advantage (van Heteren et al . 2016; Gálvez‐López & Cox 2022). As such, juvenile cave bears were likely less effective masticators than fully grown cave bears.…”
Section: Discussionmentioning
confidence: 99%
“…A longer coronoid process and an rostrally expanded masseteric fossa correspond to increased muscle attachment areas and longer in‐levers, which is indicative of a higher mechanical lever advantage (van Heteren et al . 2016; Gálvez‐López & Cox 2022). As such, juvenile cave bears were likely less effective masticators than fully grown cave bears.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies in which species and sex distinctions are made on the mandible with GM (Demiraslan et al, 2021; Demircioğlu et al, 2021; Gálvez‐López & Cox, 2022). These studies showed that there are distinctive shape differences in the mandible between species.…”
Section: Introductionmentioning
confidence: 99%